Analisis Usahatani Bawang Merah Di Desa Simamora, Kecamatan Baktiraja, Kabupaten Humbang Hasundutan, Provinsi Sumatera Utara - Sitohang, Maryanti; Nainggolan, Mai Fernando (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
Shallots are an agricultural commodity that has a significant contribution to the economy because it has high economic value and is included in the group of agricultural products that control inflation. This research aims to analyze shallot farming income, and analyze what factors influence shallot farming income in Simamor Village, Baktiraja District, Humbang Hasundutan Regency, North Sumatra Province. The data collected is in the form of primary and secondary data. The sampling method for this research is the Simple Random Sampling method using Slovin with the number of samples in this research being 38. Data analysis was carried out by looking for net income and using multiple linear regression tests and multicollinearity tests. The results of the research show that the net income for shallots is IDR 30,661,617,651/ha/mt and shows that the factors of fertilizer costs, production yields, and selling prices influence the income of shallot farming.